The Role of Entrepreneurship Education to Increase Entrepreneurial Intention among University Students - Indriyani, Ratih; Kristanto, Kristanto (STAI Miftahul Ula Nganjuk, 2021)
This study aims to determine whether there is an influence of entrepreneurship education, entrepreneurial self-efficacy, and skills on entrepreneurial intentions in students in Yogyakarta. The research method used is quantitative. The sampling technique used in this research is simple random sampling. This research was conducted by distributing questionnaires to 156 students in Yogyakarta. The data was processed using a structural model equation approach with the technique Partial Least Square. The results of this study indicate that entrepreneurship education has a significant effect on entrepreneurial self-efficacy, entrepreneurial skills, and entrepreneurial intentions; entrepreneurial self-efficacy and entrepreneurial skills have a significant influence on entrepreneurial intentions.